Development of an Analytical Method for the Determination of Cymoxanil in Potato Flour Samples by High Performance Liquid Chromatography - Tuğçe Unutkan Gösterişli (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, a high performance liquid chromatography-ultraviolet detection method was introduced for the detection of cymoxanil. The experimental parameters of the procedure were thoroughly evaluated. Cymoxanil was eluted by ammonium formate buffer (50.0 mM, pH 4.0):acetonitrile (55:45 v/v) as mobile phase. Under the optimal conditions, the limits of detection and quantification (LOD and LOQ) were found as 7.4 – 24.8 µg kg-1, which allows trace determination of pesticides in food samples. Proposed method was then implemented for the determination of selected fungicide in potato flour samples with acceptable % recoveries in the range of 81.4–112.9%, while the values of relative standard deviation (RSD) were below 10% showing a satisfactory applicability for cymoxanil in such complex real samples matrix.